2023
DOI: 10.3390/antiox12020271
|View full text |Cite
|
Sign up to set email alerts
|

Methane Admixture Protects Liver Mitochondria and Improves Graft Function after Static Cold Storage and Reperfusion

Abstract: Mitochondria are targets of cold ischemia-reperfusion (IR), the major cause of cell damage during static cold preservation of liver allografts. The bioactivity of methane (CH4) has recently been recognized in various hypoxic and IR conditions as having influence on many aspects of mitochondrial biology. We therefore hypothesized that cold storage of liver grafts in CH4-enriched preservation solution can provide an increased defence against organ dysfunction in a preclinical rat model of liver transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The first key difference between these experiments is that livers analyzed in the present study have variable and notably longer cold ischemic times and have undergone reperfusion in the form of NMP, while in the previous study no machine perfusion was applied. This finding is in line with a recent study of Horváth et al [ 22 ]. They investigated the effect of prolonged CIT and subsequent normothermic isolated perfusion on mitochondrial function in DCD rat livers.…”
Section: Discussionsupporting
confidence: 94%
“…The first key difference between these experiments is that livers analyzed in the present study have variable and notably longer cold ischemic times and have undergone reperfusion in the form of NMP, while in the previous study no machine perfusion was applied. This finding is in line with a recent study of Horváth et al [ 22 ]. They investigated the effect of prolonged CIT and subsequent normothermic isolated perfusion on mitochondrial function in DCD rat livers.…”
Section: Discussionsupporting
confidence: 94%
“…In this Special Issue, Keppler et al [57] showed the capability of eukaryotic cells to synthesize CH4 via a radical-driven process. In addition, Horváth et al [58] demonstrated that although CH4 is synthesized in a radical-dependent way, it protects mitochondrial function and maintains Ca 2+ homeostasis. These data suggest that antioxidants can affect physiological CH4-mediated signaling.…”
Section: Antioxidants Interfere With Cell Signalingmentioning
confidence: 99%
“…Furthermore, DN solutions lack calcium and are administered in a ratio of four parts crystalloid to one part blood [22]. Notably, the perfusion volume of HTK solution during CABG procedures is higher (2000ml vs. 1000ml) compared to DN solution, resulting in sodium and calcium levels below the normal range for the HTK group and within normal limits for the DN group [23].…”
Section: Cardioplegia Solutions and Hyponatremia And Ionized Calciummentioning
confidence: 99%